Death Across Cultures Death and Dying in Non-Western Cultures - Selin, Helaine; Rakoff, Robert M. (Science Across Cultures: The History of Non-Western Science, 2019)
Death Across Cultures: Death and Dying in Non-Western Cultures, explores death practices and beliefs, before and after death, around the non-Western world. It includes chapters on countries in Africa, Asia, South America, as well as indigenous people in Australia and North America. These chapters address changes in death rituals and beliefs, medicalization and the industry of death, and the different ways cultures mediate the impacts of modernity. Comparative studies with the west and among countries are included. This book brings together global research conducted by anthropologists, social scientists and scholars who work closely with individuals from the cultures they are writing about.